2021
DOI: 10.3390/s21072258
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Reported and Accelerometer-Based Estimates of Physical Activity in Portuguese Older Adults

Abstract: Accurate assessment of physical activity (PA) is crucial in interventions promoting it and in studies exploring its association with health status. Currently, there is a wide range of assessment tools available, including subjective and objective measures. This study compared accelerometer-based estimates of PA with self-report PA data in older adults. Additionally, the associations between PA and health outcomes and PA profiles were analyzed. Participants (n = 110) wore a Xiaomi Mi Band 2® for fifteen consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
(114 reference statements)
0
9
1
Order By: Relevance
“…Shiroma et al [34] also found a discrepancy between the range of moderate and vigorous physical activities that Actigraph measured, suggesting that the Actigraph might be inadequate to measure the PA of individuals who engage mainly in vigorous activities. However, Domingos et al [35] found that vigorous physical activities measured using the Actigraph were higher than those measured using the self-reported questionnaire and concluded that disagreement with vigorous PA might have a systematic bias and, in part, it was inconsistent with the results of this study.…”
Section: Discussioncontrasting
confidence: 82%
“…Shiroma et al [34] also found a discrepancy between the range of moderate and vigorous physical activities that Actigraph measured, suggesting that the Actigraph might be inadequate to measure the PA of individuals who engage mainly in vigorous activities. However, Domingos et al [35] found that vigorous physical activities measured using the Actigraph were higher than those measured using the self-reported questionnaire and concluded that disagreement with vigorous PA might have a systematic bias and, in part, it was inconsistent with the results of this study.…”
Section: Discussioncontrasting
confidence: 82%
“…In the present study, no correlation was observed between direct and indirect methods; however, this may have been influenced by the age of the study participants, as all were over 60 years. A study comparing the IPAQ long version to commerciallyavailable wearable activity tracker in a group of Portuguese older adults found considerable variation between self-reported and direct measurements (Domingos et al, 2021). The authors conclude that although accelerometry may be more a more accurate method, self-report questionnaires could provide valuable information about the context of the activity.…”
Section: Discussionmentioning
confidence: 97%
“…The wearable activity tracker selection was based on a review of the characteristics of several different commercially available devices on the market ( El-Amrawy and Nounou, 2015 ; Liang et al, 2018 ; Xie et al, 2018 ). The selection criteria included the popularity in the wearable healthcare devices market, availability, continuous monitoring of PA without a smartphone, price, battery life, various sensors data captured, and ability to export data ( Domingos et al, 2021a ). The Xiaomi Mi Band 2 ® was selected because it offers the best price-quality ratio, has an estimated battery life of almost 30 days, is ergonomic, accessible, and easy to operate.…”
Section: Methodsmentioning
confidence: 99%
“…Data collected from this set of participants were also included in previous studies that evaluated the user experience of older adults with wearable devices (Domingos et al, 2020(Domingos et al, , 2021a.…”
Section: Participantsmentioning
confidence: 99%